Akselerasi Kinerja Bisnis UMKM di Kecamatan Kendal Melalui Pemanfaatan Teknologi Digital Payment - Fia Ekanitantri Agustia Rahman; Siti Kholifah (LPPM Universitas Sains dan Teknologi Komputer, 2026)
The rapid acceleration of financial technology has shifted the operational paradigm of micro, small, and medium enterprises (MSMEs). This study investigates the impact of digital payment adoption on the business performance of MSMEs in Kendal District. Employing a quantitative approach, data were collected from 100 MSME owners across various sectors, predominantly from the trade, services, and culinary industries. Data analysis was performed using multiple linear regression and partial hypothesis testing (t-test) via SPSS. The findings reveal that digital payment usage exerts a positive and significantly profound influence on MSME performance, with a coefficient of determination (R2) reaching 94.5%. Specifically, the integration of digital transactions, led by QRIS (49%), has successfully accelerated sales volume, enhanced transaction speed, and elevated customer satisfaction. Beyond technical efficiency, this study highlights a cultural shift in Kendal’s local economy, where digital tools act as a